Single microstrip patch antenna with aperture coupler fed technique at 2.4 GHz for wireless communication / Ilyano Jusof - Jusof, Ilyano (2012)
This paper presents the basic design of the single microstrip rectangular patch antenna with aperture coupler fed technique which operates at 2.4GHz frequency. The microstrip rectangular patch antenna with aperture coupler feeding was designed and simulated using CST Microwave Environment software 2009 (Computer Simulation Technology 2009) and to be used for wireless application. The basic designation is the aperture coupled microstrip antenna couples the patch antenna with microstripline through an aperture. The performance results of the designed and simulation antenna was analyzed in terms of return loss (Sll) in dB, VSWR, radiation pattern and gain. The most effective way to increase the return loss is to optimize the patch shape, feed shape and slot shape. With chosen suitable combination substrate and perfect match between them, it will give an optimum and the best improvement of the radiation pattern.